Free-roaming mobile agent (FRoMA) protection against multiple attacks. (4th August 2009) - Venkatesan, S.; Chellappan, C.
Network traffic is the major concern in distributed computing. To reduce this, mobile agent technology is used in the distributed environment. Even though mobile agent is used in the distributed environment, the traffic is not reduced more due to more number of dispatches or migration from the source host to the remote hosts. To reduce the traffic more than the simple mobile agent, the free roaming mobile agent model is introduced in the network. Despite from its advantage, free roaming mobile agent faces various security issues like colluded attacks, truncation attacks and more. We proposed the id verification model to protect the free roaming mobile agent against the colluded and truncation attacks. This paper also proposes the recovery model for free-roaming mobile agent and its collected offers by the K-response model. It is to improve the fault tolerance of the agent failure or agent occupied by the malicious host by identifying whether the agent is dispatched to next host or not.